GERAKAN ISLAM MODERN KOMUNITAS ARAB DI SOLO, 1912-1942 - Akmal Aji Hidayatullah; Yusril Fahmi Adam (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2022)
The modern Islamic movement is a movement that existed in the early 20th century. This term is often used to describe the change in life systems from the traditional Islamic system to a more modern system. This movement is characterized by Islamic activities through modern organizations, newspapers, modern education, new ideologies and re-questioning the position of women in religion. Arabs living in the Dutch East Indies participated in the process of this movement, especially in Solo in the early 20th century. Therefore, this paper aims to explain how the process of the modern Islamic movement carried out by Arabs in Solo in 1912 -1942. This study uses historical methods, sociological approachment, and modernitation theory. The results of this study indicate that Arabs in Solo were initially involved with the local movement in 1912-1930. Then After